2018
DOI: 10.3892/ijo.2018.4506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-caryophyllene on arginine ADP-ribosyltransferase 1-mediated regulation of glycolysis in colorectal cancer under high-glucose conditions

Abstract: Type 2 diabetes mellitus (T2DM) is associated with an increased risk of the development of colorectal cancer (CRC). A previous study revealed that the levels of arginine-specific mono-ADP-ribosyltransferase 1 (ART1) in CRC tissues from patients with T2DM were higher than in non-diabetic patients. Hyperglycemia, which is a risk factor of cancer, is a common feature of T2DM; however, the effects of ART1 on glycolysis and energy metabolism in CRC cells under high-glucose conditions remains to be elucidated. β-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…The overexpression of ART1 probably increases glycolysis and energy metabolism, thus regulating the protein kinase B/mammalian target of rapamycin/c-Myc signaling pathway and the expression of glycolytic enzymes. This suggests that BCPO may be a potential treatment for this kind of carcinoma [51].…”
Section: β-Caryophyllene and Cancermentioning
confidence: 93%
“…The overexpression of ART1 probably increases glycolysis and energy metabolism, thus regulating the protein kinase B/mammalian target of rapamycin/c-Myc signaling pathway and the expression of glycolytic enzymes. This suggests that BCPO may be a potential treatment for this kind of carcinoma [51].…”
Section: β-Caryophyllene and Cancermentioning
confidence: 93%
“…Furthermore, it produces cytoprotective effects by modulating oxidative stress, apoptosis and inflammation [38][39][40][41], through the interference with different inflammatory pathways, such as the inducible nitric oxide synthase (iNOS), tumor necrosis factor-alfa (TNF-α) and nuclear factor-κB (NF-κB) [37]. Also, it exhibited chemopreventive properties, such as genoprotective and antiproliferative ones, by inhibiting DNA damage and STAT3 (signal transducer and activator of transcription 3) activation induced by environmental pollutants [31,32,42,43] and through affecting multiple cascades involved in cancer growth [37,[44][45][46][47]. Similar properties have been also reported for the metabolite β-caryophyllene oxide [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [ 45 ] suggested, also, that β-caryophyllene could be used as a therapeutic target for the treatment of diabetic patients, since this terpene acts at the level of arginine-specific mono-ADP-ribosyltransferase 1. Moreover, β-caryophyllene oral administration at a dose of 200 mg/kg induced a reduction of glucose, increase of plasma insulin levels, and improvement of altered activities of carbohydrate metabolic enzymes [ 46 ].…”
Section: Resultsmentioning
confidence: 99%